The SMEs perception of financial risks in the context of cluster cooperation - Katarína Havierniková; Marcel Kordoš (Quantitative Finance and Economics, 2019)
Although, the Small and Medium-sized enterprises are the most numerous members in clusters, many of their representatives do not know benefits from this type of cooperation and they perceive it as a risky in general. Whereby, the clusters present one form of sustainable development of SMEs business. The focus of this paper is to provide an analytical framework in which the SMEs' perception of selected risk indicators is investigated by characterizing the financial risks related to cluster cooperation. While risk indicators are presented through five main categories of financial risks. To gain the main aim of this paper following research methods were used:Chi square test to compare statistical significant differences between the stated groups of respondents, Z-score to investigate the statistically significant differences in individual responses, Pareto analysis to determine the most important risk indicators and Key risk matrix to assess the level of risk indicators. The results have showed, that most important risk indicators are from category of business risks and they related with main issues of cluster cooperation:human factor failure, legal risk and risk related to lose of own reputation. These results highlighted the importance of financial risks that may be necessary for SMEs, other stakeholders and policy makers to overcome the barriers in development of cluster cooperation. The added value of this paper is the comparison of SMEs' perception of risk indicators from several points of view and final evaluation is connected and compared with the perception of those SMEs that have or had experience with cluster cooperation.